Alexander Zinoviev: An Introduction to His Work - Kirkwood, Michael. author. aut Link
XIV, 272 p.
Keywords: Zinoviev's twin themes are the nature of Soviet communist society and the West's inability to understand it. It is the purpose of this book to trace the development of his thinking via a chronological analysis of his most important works.